Y = 4xz – x^4 – z^4

(Squiggly d’s btw)

Dy/dx = 4z – 4x^3

Dy/dz = 4x – 4z^3

D2y/dx2 = -12x^2

D2y/dz2= -12z^2

How can I work out d2y/dxdz or d2y/dzdx which is the same thing….?

(Squiggly d’s btw)

Dy/dx = 4z – 4x^3

Dy/dz = 4x – 4z^3

D2y/dx2 = -12x^2

D2y/dz2= -12z^2

How can I work out d2y/dxdz or d2y/dzdx which is the same thing….?

Other Links From
Problem Solved:

Options

## All Comments

(21) Jump to unreadPost a commentmazel tov

a constant or a function z(x) that consists of x?

edit: i think z may be a function of x and y, z(x,y)? otherwise d2y/dxdy = 0?

Edited By: mug51 on May 19, 2011 16:31not homework, just doing this for fun oO

a constant or a function z(x) that consists of x?

edit: i think z may be a function of x and y, z(x,y)? otherwise d2y/dxdy = 0?

Partial differentiation question.

Y(X,Z) = 4xz – x^4 – z^4

not homework, just doing this for fun oO

ok, let you off......geek :D

not homework, just doing this for fun oO

oO......you do head wrecking math for fun ?!?!

yes....lol

is it 4 or -12?

is it 4 or -12?

4, as d^2y/dxdz is d(dy/dx)/dz i.e dy/dx differentiated w.r.t z

its -12 as i got tails

is it 4 or -12?

4, as d^2y/dxdz is d(dy/dx)/dz i.e dy/dx differentiated w.r.t z

oh alright. Thanks....!

(4xz + 16xz^3 - 16x^4 - 16z^4)/d^2y =dxdzThen rearranging i get (d^2y)^2/above = your equation, just squared...

So the answer I get finally, is the square root of the answer in bold at the top ;)

:D;)

Too hard. Can I stand on yours instead?

ha ha lol.

stop looking at my threads!

these are tooo easy now.

ha ha!